Correction to: A Regular Integral Equation Formalism for Solving the Standard Boussinesq’s Equations for Variable Water Depth - Jang, T. S. (Journal of scientific computing, 2019)
The author would like to correct an error in calculation of the Eq. (A.2.8) in Appendix A.2 of the original article. The correct equation is as follows: